FACTORS THAT INFLUENCE WORK DICIPLINE - Yulius, Yosandi (Dinasti Publisher, 2022)
This study aims to examine the effect of Leadership and Work Motivation on Work Dicipline. This study uses explanatory quantitative research on 30 manufacturing company in DKI Jakarta with 80 respondents processed using the SEM-PLS approach. The results of the study indicate that Leadership directly influences Work Dicipline on manufacturing company in DKI Jakarta and Work Motivation directly influence Work Dicipline manufacturing company in DKI Jakarta.